2022
DOI: 10.1016/j.avsg.2022.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Treating Peripheral Arterial Occlusive Disease and Acute Limb Ischemia During a COVID-19 Pandemic in 2020

Abstract: Objective For many surgeons the outbreak of SARS-CoV-2 meant a downscaling of surgical interventions. The aim of this study was to investigate the impact of the measures taken on the care for patients with peripheral arterial disease (PAOD) and acute limb ischemia (ALI). Methods A retrospective analysis of the vascular practices of two major teaching hospitals in the Netherlands was performed. All interventions and outpatient visits for PAOD or ALI in 2020 were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Equally impressive was the relative increase in the proportion of patients with acute limb ischemia, i.e., a vascular emergency, from 24.6% to 47.5% [ 12 ]. In contrast, in their evaluation of two large hospitals in the Netherlands, Exelmans et al observed no significant decrease in the number of patients treated throughout 2020, but a relative increase in higher PAD stages and acute limb ischemia with a subsequent increase in major amputations [ 15 ]. Thus, care for critically ill patients does not seem to be that compromised and the outcome acceptable?…”
Section: Discussionmentioning
confidence: 99%
“…Equally impressive was the relative increase in the proportion of patients with acute limb ischemia, i.e., a vascular emergency, from 24.6% to 47.5% [ 12 ]. In contrast, in their evaluation of two large hospitals in the Netherlands, Exelmans et al observed no significant decrease in the number of patients treated throughout 2020, but a relative increase in higher PAD stages and acute limb ischemia with a subsequent increase in major amputations [ 15 ]. Thus, care for critically ill patients does not seem to be that compromised and the outcome acceptable?…”
Section: Discussionmentioning
confidence: 99%